The value of serum cystatin c in predicting acute kidney injury after cardiac surgery: A systematic review and meta-analysis. - PeiQiang Peng; Xiao Chen Fu; YueTing Wang; XuFei Zheng; Linfang Bian; Nuer Zhati; Shuang Zhang; Wei Wei (PLoS ONE)
Objective This study aims to review relevant research and assess the diagnostic value of serum cystatin C (CysC) for post-cardiac surgery acute kidney injury (PCSAKI). Method We searched databases (PubMed, Embase, Cochrane, WanFang, CNKI, VIP) for literature published up to January 10, 2024. Quality was assessed using Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2). Extracted data from eligible studies and summarized sensitivity, specificity, and area under the curve (AUC) values. Results A total of 24 studies involving 3,427 patients were included. The estimated diagnostic sensitivity of CysC for PCSAKI was 0.67 (95% CI, 0.57-0.76), with a specificity of 0.87 (95% CI, 0.81-0.91). The positive likelihood ratio (+LR) was 5.17 (95% CI, 3.45-7.73), and the negative likelihood ratio (-LR) was 0.38 (95% CI, 0.28-0.51). The diagnostic odds ratio (DOR) was 14 (95% CI, 7-26), the diagnostic score (DS) was 2.62 (95% CI, 1.99-3.24), and AUC was 0.86 (95% CI, 0.83-0.89). The sub-analysis results indicate that gender distribution, serum storage temperature, CysC detection method, and detection time all have a significant impact on sensitivity and specificity. Conclusion CysC has high specificity and good sensitivity in diagnosing PCSAKI during the perioperative period, with better detection results 24 hours before surgery, making it suitable for early detection. However, whether and how CysC is commonly used in clinical diagnosis still requires further research and clinical trials.